Anthropometric Dividends of Czechoslovakia's Break Up - Joan Costa-i-Font; Lucia Kossarova (London School of Economics and Political Science (LSE), European Institute, 2015)
Processes of transition to democracy and country break up stand out as ideal experiments to estimate the impact of wide institutional reform on well-being. Changes in population heights are regarded as virtuous pointers of well-being improvements in psycho-social environments, which improve with democracy. We analyzed a unique dataset containing individual heights in the Czech Republic and Slovakia to measure the retrospective wellbeing effects of the two transitions to liberal democracy and capitalism after the split up of Czechoslovakia. An additional year spent under democracy increases height by 0.286cm for Slovaks and 0.148cm for Czechs. Results were robust to using an alternative dataset and suggest that although transition paths differ across the two countries, the absolute height gap between Slovaks and the Czechs did not change. Slovaks benefited more than the Czechs in the bottom and mid tercile.
Keywords: 330; height; democracy; transition; secession; Czechoslovakia; Blinder-Oaxaca decomposition; height dimorphism